Effect of Velocity and Contact Stress Area on the Dynamic Behavior of the Spinal Cord Under Different Testing Conditions - Jin, Chen; Zhu, Rui; Xu, Meng-lei; Zheng, Liang-dong; Zeng, Hui-zi; Xie, Ning; Cheng, Li-ming (Frontiers in Bioengineering and Biotechnology, 2022)
Knowledge on the dynamic behavior of the spinal cord under different testing conditions is critical for our understanding of biomechanical mechanisms of spinal cord injury. Although velocity and contact stress area are known to affect external mechanical stress or energy upon sudden traumatic injury, quantitative investigation of the two clinically relevant biomechanical variables is limited. Here, freshly excised rat spinal-cord-pia-arachnoid constructs were tested through indentation using indenters of different sizes (radii: 0.25 mm, 0.50 mm, and 1.00 mm) at various loading rates ranging from 0.04 to 0.20 mm/s. This analysis found that that the ex vivo specimen displayed significant non-linear viscoelasticity at <10% of specimen thickness depth magnitudes. At higher velocity and larger contact stress area, the cord withstood a higher peak load and exhibited more sensitive mechanical relaxation responses (i.e., increasing amplitude and speed of drop in peak load). Additionally, the cord became stiffer (i.e., increasing elastic modulus) and softer (i.e., decreasing elastic modulus) at higher velocity and larger contact stress area, respectively. These findings will improve our understanding of the real-time complex biomechanics involved in traumatic spinal cord injury.